2006
DOI: 10.1002/anie.200503028
|View full text |Cite
|
Sign up to set email alerts
|

The [Ga2(C5Me5)]+ Ion: Bipyramidal Double‐Cone Structure and Weakly Coordinated, Monovalent Ga+

Abstract: Partial protolysis of GaCp* with [H(OEt2)2]+[BArF]− afforded the GaI compound [Ga2Cp*]+[BArF]− (see structure). Experimental and computational studies confirm the mainly ionic structure of the cation, in which the Ga+ ions are only weakly covalently stabilized by a bridging Cp* ligand. Initial experiments point to the interesting synthetic potential of this compound as a source for Ga+ in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…[273] Although the heavier Group 15 complexes of the type [Cp X 2 E] + (where E = As,S b, or Bi;X= C 5 Me 5 or C 5 H 2 t Bu 3 )h ave been reported with the relatively simple WCAs[ BF 4 ] À [357] and [AlCl 4 ] À , [358][359][360] the phosphorus analogue was reported only relatively recently.T wo equivalents of the Lewis acid PhF!Al(OR F ) 3 were used to abstract ac hloride ligand from (Cp*) 2 PCl to form [(Cp*) 2 P]-[(R F O) 3 Al-Cl-Al(OR F ) 3 ]( Cp* = C 5 Me 5 ). [361] Dodecamethylsilicocene Si(C 5 Me 5 ) 2 was shown to react with the Brønsted acid [Me 5 C 5 H 2 ][B(C 6 F 5 ) 4 ]t oy ield the silicocenium cation [Si(C 5 Me 5 )][B(C 6 F 5 ) 4 ], which shows no close cation-anion interactions in the solid state. [145] Subvalent Cp X Complex Cations: Theu se of cyclopentadienyl and arene ligands for the stabilization of low oxidation state main group elements has developed into ar ich area of main group chemistry,and the use of WCAshas permitted the isolation of cationic low oxidation state main group complexes.The reaction of the subvalent gallium complex Cp*Ga with half an equivalent of the 4 ], in which the gallium atoms are located above and below the Cp* ring.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[273] Although the heavier Group 15 complexes of the type [Cp X 2 E] + (where E = As,S b, or Bi;X= C 5 Me 5 or C 5 H 2 t Bu 3 )h ave been reported with the relatively simple WCAs[ BF 4 ] À [357] and [AlCl 4 ] À , [358][359][360] the phosphorus analogue was reported only relatively recently.T wo equivalents of the Lewis acid PhF!Al(OR F ) 3 were used to abstract ac hloride ligand from (Cp*) 2 PCl to form [(Cp*) 2 P]-[(R F O) 3 Al-Cl-Al(OR F ) 3 ]( Cp* = C 5 Me 5 ). [361] Dodecamethylsilicocene Si(C 5 Me 5 ) 2 was shown to react with the Brønsted acid [Me 5 C 5 H 2 ][B(C 6 F 5 ) 4 ]t oy ield the silicocenium cation [Si(C 5 Me 5 )][B(C 6 F 5 ) 4 ], which shows no close cation-anion interactions in the solid state. [145] Subvalent Cp X Complex Cations: Theu se of cyclopentadienyl and arene ligands for the stabilization of low oxidation state main group elements has developed into ar ich area of main group chemistry,and the use of WCAshas permitted the isolation of cationic low oxidation state main group complexes.The reaction of the subvalent gallium complex Cp*Ga with half an equivalent of the 4 ], in which the gallium atoms are located above and below the Cp* ring.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[145] Subvalent Cp X Complex Cations: Theu se of cyclopentadienyl and arene ligands for the stabilization of low oxidation state main group elements has developed into ar ich area of main group chemistry,and the use of WCAshas permitted the isolation of cationic low oxidation state main group complexes.The reaction of the subvalent gallium complex Cp*Ga with half an equivalent of the Brønsted acid [H(OEt 2 ) 2 ][B-(Ar CF3 ) 4 ]r esults in the formation of the unusual bipyramidal double cone structure of [Ga 2 Cp*][B(Ar CF3 ) 4 ], in which the gallium atoms are located above and below the Cp* ring. [361] Dodecamethylsilicocene Si(C 5 Me 5 ) 2 was shown to react with the Brønsted acid [Me 5 C 5 H 2 ][B(C 6 F 5 ) 4 ]t oy ield the silicocenium cation [Si(C 5 Me 5 )][B(C 6 F 5 ) 4 ], which shows no close cation-anion interactions in the solid state. [276] Furthermore,it has subsequently been demonstrated that the reaction of Si(C 5 Me 5 ) 2 with the Brønsted acid [H(OEt 2 ) 2 ][Al(OR F ) 4 ] results in the formation of [Si(C 5 Me 5 )] + supported by the [Al(OR F ) 4 ] À ion.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In this respect, the facile access to an In[SO 3 CF 3 ] salt was a step ahead and allowed for the characterization of the first In + crown‐ether complexes . However, related chemistry with Ga + did not work and the only published compound which seemed likely to be a suitable starting material for coordination chemistry was the [Ga 2 Cp*] + cluster cation—with the complication of providing one surplus equivalent of neutral GaCp* per used Ga + (Cp*=C 5 Me 5 ). The subsequent facile access to arene complexes of In + and Ga + salts with the non‐reactive weakly coordinating anion (WCA) [Al(OR F ) 4 ] − opened a new starting point to interesting coordination chemistry with a variety of σ‐donors including phosphines, carbenes, pyridines, and also crown ethers .…”
Section: Figurementioning
confidence: 99%
“…Recently, Fischer and co-workers showed that the gallium(I) salt [Ga 2 Cp*] + [B(Ar F ) 4 ] À can be prepared and used as a well-defined starting material for gallium(I) chemistry. [8,9] With this salt, gallium(I) was transferred to platinum and ruthenium, forming for example [Pt(Ga)(GaCp*) 4 ] + [B-(Ar F ) 4 ] À . [10,11] However, the synthesis of [Ga 2 Cp*] + [B(Ar F ) 4 ] À is not trivial, in that it involves multiple steps, and the atom efficiency of this gallium(I) source is less than perfect, as a molecule of Cp*Ga is lost for every gallium(I) delivered to a substrate.…”
mentioning
confidence: 99%